2015
DOI: 10.1016/j.jare.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of rosuvastatin and amlodipine in human plasma using tandem mass spectrometry: Application to disposition kinetics

Abstract: The liquid chromatography–tandem mass spectrometric assay method for the simultaneous determination of rosuvastatin and amlodipine in human plasma using deuterated analogs as internal standards has been developed and validated. The analytes were extracted from 100 μL aliquots of human plasma via liquid–liquid extraction using a mixture of ethyl acetate and n-hexane (80:20, v/v) as an extraction solvent. The optimized mobile phase was composed of 0.1% formic acid in 5 mM ammonium acetate, methanol, and acetonit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…However, other analytical and bioanalytical methods demonstrated higher sensitivity values ranging from 0.05 mg/mL to 30 mg/ mL. Table 4 [56,[108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125] shows the LC-MS/MS methods developed for ROS analysis alone or in combination with other drugs determined in biological fluids. Most LC-MS/MS analyses were performed in positive ion mode (ESI C ) for the quantification of ROS in human plasma.…”
Section: Methodsmentioning
confidence: 99%
“…However, other analytical and bioanalytical methods demonstrated higher sensitivity values ranging from 0.05 mg/mL to 30 mg/ mL. Table 4 [56,[108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125] shows the LC-MS/MS methods developed for ROS analysis alone or in combination with other drugs determined in biological fluids. Most LC-MS/MS analyses were performed in positive ion mode (ESI C ) for the quantification of ROS in human plasma.…”
Section: Methodsmentioning
confidence: 99%
“…A literature review revealed several bio‐analytical methods reported for ROS (Braga, Mancila, Cassella, & Pacheco, ; Caglar & Toker, ; Darwish & Al‐malaq, ; J. Gao, Zhong, Duan, & Chen, ; C K Hull, Penman, Smith, & Martin, ; Caroline K. Hull, Martin, Warwick, & Thomas, ; Hussain, Patel, & Tan, ; Kallem, Karthik, Chakradhar, & Mullangi, ; T. R. Kumar et al, ; Lan et al, ; H. K. Lee, Ho, Hu, Tomlinson, & Wong, ; MacWan, Ionita, & Akhlaghi, ; Oudhoff, Sangster, Thomas, & Wilson, ; Xu, Ruan, Yuan, & Jiang, ) and CAN (Gao et al, ; Jeon et al, ; Kondo, Yoshida, Yoshimura, Motohashi, & Tanayama, ; J. W. Lee et al, ; Lou, Ruan, & Jiang, ; Miyabayashi, Okuda, Motohashi, Izawa, & Yashiki, ; Prajapati, Patel, Chauhan, Patel, & Patel, ; Stenhoff, Lagerström, & Andersen, ) individually or in combination with other drugs like pioglitazone, hydrochlorothiazide, ciprofloxacin, metformin, etc., using either HPLC or LC–MS/MS (Arayne, Sultana, & Tabassum, ; Pp. Kumar, Murthy, & Basaveswara Rao, ; Narapusetti, Bethanabhatla, Sockalingam, Repaka, & Saritha, ; Nasir et al, ; Shah et al, ; Trivedi, Kallem, Mullangi, & Srinivas, ; Varghese & Ravi, ; Vittal et al, ; Bharathi, Hotha, Chatki, Satyanarayana, & Venkateswarlu, ; Gonzalez, Lopez, Alonso, & Jimenez, ; Kumari Karra, Rao Pilli, Kumar Inamadugu, & Seshagiri Rao, ; Nie et al, ; Singh, Lokhandae, Dwivedi, Sharma, & Dubey, ).…”
Section: Introductionmentioning
confidence: 99%
“…Literature survey shows that RP-HPLC stability indicating methods for rosuvastatin alone or with combination [2], LC-MS/MS methods for plasma for rosuvastatin alone or with metabolites/combination of other drugs [3][4][5][6][7][8][9][10][11][12][13][14][15][16], LC-MS/MS methods for plasma for aspirin alone or with metabolites/combination of other drugs [17][18][19][20][21][22][23][24][25] are reported. It is noted that method for simultaneous estimation of RVT with metabolites and ASP with metabolite is not available.…”
Section: Introductionmentioning
confidence: 99%
“…Potassium fluoride was used as a stabilizer, to prevent the hydrolysis of ASP to SLA while L-ascorbic acid is used to as stabilizer to prevent the inter conversion between RVT to RVL and vice versa. We had used switch over polarity concept [26] in single method, to achieve required sensitivity and selectivity. SPE method was used to clean up the plasma samples, to avoid the matrix effect and to achieve maximum recovery.…”
Section: Introductionmentioning
confidence: 99%